IMPLEMENTATION OF CARPATHIAN CONVENTION STANDARDS ON THE NORTHERN BUKOVINA TERRITORY - Солодкий, В.Д.; Беспалько, Руслан; Казімір, Іван (ACTA OECOLOGICA CARPATICA, 2014)
The current paper contemplates the sustainable development of the implementation standards that are reflected in the territory of Northern Bukovina on the basis of the Carpathian Convention principles. In this region the conducted work concerned the implementation of ecological practices for forest, agricultural and water farms on the general watershed-ecosystem basis, and also the achievement of a balanced territorial and functional
Keywords: Northern Bukovina; sustainable development; Carpathian Convention; system approach; biodiversity preservation; Ukrainian-Romanian cooperation